Pathogenicity virulence of Beauveria spp. and biosafety of the BbMQ strain on adult ectoparasitic beetles, Dastarcus helophoroides Fairmaire (Coleoptera: Colydiidae) - Zhou, Youjun; Lu, Ciding; Chen, Zhenghao; Ye, Shuting; Fang, Xinyuan; Zhang, Zhuhe; Cai, Shouping; Zhang, Feiping; Liang, Guanghong (Frontiers in Veterinary Science, 2023)
Beauveria spp. and Dastarcus helophoroides Fairmaire adults were simultaneously released to attack elder larvae or pupae of Monochamus alternatus in pine forests in China. However, little is known about the pathogenicity virulence and biosafety of Beauveria spp. to beneficial adults of D. helophoroides, and specific Beauveria bassiana (Bb) strains should be selected for synthetic release together with D. helophoroides. A total of 17 strains of Beauveria spp. were collected, isolated, and purified, then their mortality, cadaver rate, LT50, spore production, spore germination rate and growth rate of D. helophoroide adults were calculated based on 0-20 days data after spore suspension and powder contact. The results showed that the lethality rate of BbMQ, BbFD, and BbMH-03 strains exceeded 50%, and the cadaver rate reached 70.6%, among which the mortality rate (82.22%), cadaver rate (47.78%), spore production (1.32×109 spores/ml), spore germination rate (94.71%), colony dimension (49.15mm2), and LT50 (10.62 d) of BbMQ strain were significantly higher than those of other strains (P<0.01), and the mortality of adults increased significantly with increased spore suspension concentration, with the highest mortality reaching 92.22%. This strain was identified as Beauveria bassiana by morphological and molecular methods, while the BbWYS strain had a minimum lethality of only 5.56%, which was safer compared to other strains to adult D. helophoroide. Consequently, the biological characteristics and pathogenicity of different Beauveria bassiana strains varied significantly in their effects on D. helophoroide adults, and the safety of different strains should be assessed when they are released or sprayed to control multiple pests in the forest. The BbMQ strain should not be simultaneously sprayed with releasing D. helophoroide adults in the same forest, while the BbWYS strain can be used in concert with D. helophoroide to synergize their effect.